2018
DOI: 10.1088/1361-6463/aab1ac
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron emission from textured surfaces

Abstract: In this work, a Monte Carlo model is used to investigate electron induced secondary electron emission for varying effects of complex surfaces by using simple geometric constructs. Geometries used in the model include: vertical fibers for velvet-like surfaces, tapered pillars for carpet-like surfaces, and a cage-like configuration of interlaced horizontal and vertical fibers for nano-structured fuzz. The model accurately captures the secondary electron emission yield dependence on incidence angle. The model sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Aside from early efforts in surface texture development to control SEE [17,18], the use of advanced characterization and new processing techniques to develop microarchitected surfaces and experimentally determine the reduction in SEE yield is relatively recent [19][20][21]. There are now numerous examples of successful designs that are seen to lower the secondary electron yield [19,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from early efforts in surface texture development to control SEE [17,18], the use of advanced characterization and new processing techniques to develop microarchitected surfaces and experimentally determine the reduction in SEE yield is relatively recent [19][20][21]. There are now numerous examples of successful designs that are seen to lower the secondary electron yield [19,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling and simulation can play an important role in predicting the expected reduction rates of SEE before a costly effort of surface texture development, fabrication, and testing needs to be mounted. Simulations involving surfaces with grooves [27], 'velvet'-like fibers [20] and open-cell structures [21] have been recently carried out, showcasing the versatility of numerical simulation but also its relatively high computational cost. In this paper, we present a two-pronged simulation approach in which SEE yields and energy spectra are precomputed for ideally flat surfaces, and are later used to describe the constitutive response at the local material point level of a discretized surface with arbitrary geometry.…”
Section: Introductionmentioning
confidence: 99%
“…We find that micro-porous surfaces result in SEE yield reductions of over 50% in the energy range experienced in Hall thrusters. This points to the suitability of these micro-architected surface concepts to mitigate SEE-related issues in compact electric propulsion devices.Keywords: Monte Carlo simulation; electron-insulator interactions; secondary electron emission; spacecraft charging Recently, demonstration designs have been developed, including surface architectures based on metal micro-spears, micro-nodules and micro-velvets [7][8][9][10][11]. See reviews on the topic for further information [5,[12][13][14][15][16].…”
mentioning
confidence: 99%
“…Many recent experimental and modeling efforts have investigated textured materials to reduce SEE. These include metallic surfaces with nm to mm-sized vertical fibers/velvet, 5,[8][9][10][11][12][13][14][15] isotropically aligned fibers/fuzz, 3,8,9,16 pores, 17,18 triangular and rectangular grooves, [19][20][21] soot particles, 22 and surface roughness. 23 For example, in a previous publication, we found that the SEE yield was reduced by more than 40% for tungsten fuzz generated in helium plasma under tokamak-like conditions when compared to smooth tungsten.…”
mentioning
confidence: 99%
“…3,5,[11][12][13][14] For example, Jin et al 5 measured a 35% reduction in SEE (i.e., from a total SEE yield of $0.89 to 0.57) for carbon velvet with D fiber ¼ 3 mm, aspect ratio A ¼ 2L fiber =D fiber ¼ 860, and packing density ¼ 87% due to electrons incident at 300 eV and 0 . Since the SEE yield is relatively flat above 200 eV, 3,5,9 it may be assumed that a nearly 35% reduction in SEE also occurs for 500 eV incident electrons. Analytical 10 and Monte Carlo [8][9][10]15,16 modeling of fibrous surfaces have confirmed that the reduction in SEE is due to trapping of emitted electrons (mostly true secondary electrons with a cosine angular distribution), especially for high aspect-ratio fibers.…”
mentioning
confidence: 99%